Representation Past Tense of the verb in Ukrainian and Italian laguages (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
Past time of the verb in the Ukrainian and in Italian languages is analyzed. Grammatical forms for expressing of the Past Time are shown. Past Tense in the Italian language has more complex structure than in Ukrainian one is proved.
Keywords: contrastive grammar; Italian and Ukrainian; verb; grammatical category of the verb time; Past Time